Prevalence and prognostic significance of malnutrition risk in patients with pulmonary tuberculosis: A hospital-based cohort study - Ma, Jiao-Jie; Guo, Yi-Jia; Li, Zhuo; Chen, Yang; He, Hong; Li, Wei-Min (Frontiers in Public Health, 2022)
Background: Prevalence and prognostic significance of malnutrition risk remain unclear in Chinese patients with pulmonary tuberculosis. We aimed to investigate the malnutrition risk in hospital patients, and explore the relationship between malnutrition risk and follow-up outcome. Methods: We conducted a hospital-based cohort study from January 2020 to December 2020. Malnutrition risk were evaluated by nutritional scales, including the nutritional risk screening 2002 (NRS-2002), controlling nutritional status score(CONUT), geriatric nutritional risk index(GNRI), and prognostic nutritional index(PNI). The primary outcome was all-cause mortality at 1 year follow-up. Malnutrition risk was calculated and the relationship between malnutrition and follow-up outcome was analyzed. We assessed the performance of malnutrition risk to predict clinical outcome in prognostic models. Results: A total of 1075 patients were included. According to NRS-2002, CONUT, GNRI, and PNI, 818(76.09%), 954(88.74%), 682(63.44%) and 364 (33.86%) patients were at risk of malnutrition, respectively. At 1-year follow-up, a total of 99 patients (9.2%) experienced death. After adjustment for risk factors, the association between severe malnutrition of CONUT (HR=4.78, 95% CI 1.14-20.11, P=0.033), GNRI (HR=3.53, 95% CI 1.70-7.34, P=0.001) or PNI (HR=2.94, 95% CI 1.76-4.88, P<0.001) and 1-year follow-up death remained significant. Addition of the nutritional scales to prognostic models improved predictive ability for death validated by the integrated discrimination index (all P<0.05). Conclusions: Malnutrition in patients with pulmonary tuberculosis was associated with increased risk of all-cause death in the long-term follow-up. Our study provides evidence supporting on admission nutrition screening in patients with pulmonary tuberculosis.